Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41594-021-00583-9
|View full text |Cite
|
Sign up to set email alerts
|

Structures of chaperone-associated assembly intermediates reveal coordinated mechanisms of proteasome biogenesis

Abstract: The proteasome mediates most selective protein degradation. Proteolysis occurs within the 20S core particle (CP), a barrel-shaped chamber with an α 7 β 7 β 7 α 7 configuration. CP biogenesis proceeds through an ordered multistep pathway requiring five chaperones, Pba1-4 and Ump1. Using S. cerevisiae, we report high-resolution structures of CP assembly intermediates by cryogenic-electron microscopy. The first structure corresponds to the 13S particle which consists of a complete α-ring, partial β-ring (β2-4), U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 41 publications
2
36
0
Order By: Relevance
“…Instead, our experiments revealed that the propeptide of the β7 precursor subunit promotes binding to Ump1 in vitro, and this interaction depended on the presence of the N-terminal 16 residues of Ump1 (Figure 5). Although the structure of the N-terminal 26 residues of Ump1 could not be resolved [17], crosslinking of its residue 19 Lys to residue 91 Lys of β6 [6] is compatible with our biochemical data as it suggests that the N-terminal domain of Ump1 is likely not too far away from the position where Pro-β7 will insert. The distance of 91 Lys of β6 to the N-terminal Thr of processed β7 in the structure of the mature 20S CP is only ~15 Å [35], indicating that the N-terminal domain of Ump1 is probably well-positioned to interact with the propeptide of incoming Pro-β7 (Figure 6).…”
Section: Ump1 N-terminal Domain Interacts With Pro-β7 To Promote 15s ...supporting
confidence: 83%
See 2 more Smart Citations
“…Instead, our experiments revealed that the propeptide of the β7 precursor subunit promotes binding to Ump1 in vitro, and this interaction depended on the presence of the N-terminal 16 residues of Ump1 (Figure 5). Although the structure of the N-terminal 26 residues of Ump1 could not be resolved [17], crosslinking of its residue 19 Lys to residue 91 Lys of β6 [6] is compatible with our biochemical data as it suggests that the N-terminal domain of Ump1 is likely not too far away from the position where Pro-β7 will insert. The distance of 91 Lys of β6 to the N-terminal Thr of processed β7 in the structure of the mature 20S CP is only ~15 Å [35], indicating that the N-terminal domain of Ump1 is probably well-positioned to interact with the propeptide of incoming Pro-β7 (Figure 6).…”
Section: Ump1 N-terminal Domain Interacts With Pro-β7 To Promote 15s ...supporting
confidence: 83%
“…Structural studies of recombinant yeast Ump1 protein showed that it behaves similar to a natively unfolded protein with little secondary structure elements [ 15 , 16 ]. Structural studies based on electron microscopy (EM) and crosslinking revealed that, in the 15S PC, Ump1 loops around the inner cavity in a stretched-out conformation at the interface between α- and β-rings [ 6 , 17 ]. Experiments that either used partial trypsin cleavage [ 5 ] or detection of an N-terminal 6His tag on Ump1 by Ni-NTA nanogold particles in electron microscopy [ 6 ] indicated that the Ump1 N terminus projects out of the β-ring opening [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using proteasome mutants that stall the assembly process, Hanna's group has been able to determine the structure of two intermediates: the 13S complex, which contains the α ring, β2‐4, Ump1, and Pba1/2; and a pre‐15S intermediate that contains the α ring, β2‐6, Ump1, and Pba1/2. The structures reveal several insights into proteasome assembly and clear up several previous misconceptions 11 . Most notably, the structures show that Ump1, which was previously believed to be unstructured and extend out of the nascent core particle, adopts an extended helical conformation and forms extensive contacts throughout the core particle, including with several β‐propeptides and Pba1.…”
Section: Structural Insights On Proteasome Assemblymentioning
confidence: 68%
“…The structures reveal several insights into proteasome assembly and clear up several previous misconceptions. 11 Most notably, the structures show that Ump1, which was previously believed to be unstructured and extend out of the nascent core particle, adopts an extended helical conformation and forms extensive contacts throughout the core particle, including with several β-propeptides and Pba1. In addition, the structures reveal novel interactions between the N-terminus of Pba1 and the interior of the core particle.…”
Section: Structural Insights On Proteasome Assemblymentioning
confidence: 91%